Transient hearing loss following administration of furosemide - Mohan Kameshwaran; Mohan Viswanathan; M, Kannappa Reddy; Muthulakshmi Bharathy; S, Katneswaran (Journal of All India Institute of Speech and Hearing)
Furosemide is a new and potent diuretic which has become very popular with physicians in the management of oedema, especially in patients with severe cardiac decompensation (e.g. Pulmonary oedema due to its substantial antihypertensive effectiveness). This study was undertaken following reports of sensorineural hearing loss in the human beings with poor kidney function, the very patient treated with these diuretics and experimental induction of deafness in guinea pigs following administrations of either Furosemide or Ethacrynic acid - another new diuretic very closely related to Furosemide in its pharmacological properties